Nanoscale investigation of enhanced electron field emission for silver ion implanted/post-annealed ultrananocrystalline diamond films. Issue 1 (December 2017) - Panda, Kalpataru; Hyeok, Jeong; Park, Jeong; Sankaran, Kamatchi; Balakrishnan, Sundaravel; Lin, I.-Nan
Abstract Silver (Ag) ions are implanted in ultrananocrystalline diamond (UNCD) films to enhance the electron field emission (EFE) properties, resulting in low turn-on field of 8.5 V/μm with high EFE current density of 6.2 mA/cm2 (at an applied field of 20.5 V/μm). Detailed nanoscale investigation by atomic force microscopy based peak force-controlled tunneling atomic force microscopy (PF-TUNA) and ultra-high vacuum scanning tunneling microscopy (STM) based current imaging tunneling spectroscopy (CITS) reveal that the UNCD grain boundaries are the preferred electron emission sites. The two scanning probe microscopic results supplement each other well. However, the PF-TUNA measurement is found to be better for explaining the local electron emission behavior than the STM-based CITS technique. The formation of Ag nanoparticles induced abundant sp2 nanographitic phases along the grain boundaries facilitate the easy transport of electrons and is believed to be a prime factor in enhancing the conductivity/EFE properties of UNCD films. The nanoscale understanding on the origin of electron emission sites in Ag-ion implanted/annealed UNCD films using the scanning probe microscopic techniques will certainly help in developing high-brightness electron sources for flat-panel displays applications.